2015
DOI: 10.1186/s12877-015-0142-9
|View full text |Cite
|
Sign up to set email alerts
|

Reablement in community-dwelling older adults: a randomised controlled trial

Abstract: BackgroundThere has been an increasing interest in reablement in Norway recently and many municipalities have implemented this form of rehabilitation despite a lack of robust evidence of its effectiveness. The aim of this study was to investigate the effectiveness of reablement in home-dwelling older adults compared with usual care in relation to daily activities, physical functioning, and health-related quality of life.MethodsThis is a parallel-group randomised controlled trial conducted in a rural municipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
225
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(244 citation statements)
references
References 27 publications
10
225
1
8
Order By: Relevance
“…Although rehabilitation may be important for individuals in their own homes, rehabilitation has traditionally not been an active part of the home care service. The evidence base concerning the effects of reablement is inconclusive, but promising 13. Four recent systematic reviews conclude that there is uncertainty regarding the effects of reablement on health and function 47.…”
Section: Introductionmentioning
confidence: 99%
“…Although rehabilitation may be important for individuals in their own homes, rehabilitation has traditionally not been an active part of the home care service. The evidence base concerning the effects of reablement is inconclusive, but promising 13. Four recent systematic reviews conclude that there is uncertainty regarding the effects of reablement on health and function 47.…”
Section: Introductionmentioning
confidence: 99%
“…Our pattern of results suggests further and broader gains in functioning may be achieved once individuals are discharged from reablement. The absence of a comparator group means we cannot attribute these improvements to reablement and they may, instead or in part, be due to non‐specific recovery processes observed after, for example, a fracture has healed (Tuntland et al, ). However, a study which did use a comparator groups found differences between groups in (practitioner‐reported) abilities to carry out extended activities of daily living (favouring the reablement group) were not observed until some months after discharge (Lewin, De San Miguel, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…I Norge er det nå naermere 200 kommuner som gjennomfører hverdagsrehabilitering (Ness, 2016). I den norske litteraturen legges det vekt på at hverdagsrehabilitering skal kjennetegnes ved tidlig og intensiv innsats i en avgrenset periode, at tiltakene skal vaere tverrfaglige, og at tiltak skal ta utgangpunkt i brukerens egne ønsker for å styrke funksjonsnivå og mestring av daglige aktiviteter i brukerens hjem/naermiljø (Tuntland, Aaslund, Espehaug, Førland, & Kjeken, 2015;Høverstad & Fürst, 2014;Tuntland & Ness, 2014;NOU, 2011).…”
Section: Bakgrunnunclassified
“…Studier viser at personene som mottar hverdagsrehabilitering oppnår en forbedring i motsetning til dem som mottar vanlige omsorgstjenester (Tuntland et al, 2015). En del betingelser må likevel vaere til stede for at hverdagsrehabilitering skal fungere optimalt: forankring i kommunens ledelse, ressurstildeling, kompetanse, kulturendring og tverrfaglig samordnet innsats (Høverstad & Fürst, 2014).…”
Section: Bakgrunnunclassified